Endoscopic prediction of submucosal invasion in Barrett’s cancer with the use of artificial intelligence: a pilot study - Ebigbo, Alanna; Mendel, Robert; Rückert, Tobias; Schuster, Laurin; Probst, Andreas; Manzeneder, Johannes; Prinz, Friederike; Mende, Matthias; Steinbrück, Ingo; Faiss, Siegbert; Rauber, David; de Souza, Luis A., Jr.; Papa, João P.; Deprez, Pierre H.; Oyama, Tsuneo; Takahashi, Akiko; Seewald, Stefan; Sharma, Prateek; Byrne, Michael F.; Palm, Christoph; Messmann, Helmut (Endoscopy, 2021)
Background The accurate differentiation between T1a and T1b Barrett’s-related cancer has both therapeutic and prognostic implications but is challenging even for experienced physicians. We trained an artificial intelligence (AI) system on the basis of deep artificial neural networks (deep learning) to differentiate between T1a and T1b Barrett’s cancer on white-light images.Methods Endoscopic images from three tertiary care centers in Germany were collected retrospectively. A deep learning system was trained and tested using the principles of cross validation. A total of 230 white-light endoscopic images (108 T1a and 122 T1b) were evaluated using the AI system. For comparison, the images were also classified by experts specialized in endoscopic diagnosis and treatment of Barrett’s cancer.Results The sensitivity, specificity, F1 score, and accuracy of the AI system in the differentiation between T1a and T1b cancer lesions was 0.77, 0.64, 0.74, and 0.71, respectively. There was no statistically significant difference between the performance of the AI system and that of experts, who showed sensitivity, specificity, F1, and accuracy of 0.63, 0.78, 0.67, and 0.70, respectively.Conclusion This pilot study demonstrates the first multicenter application of an AI-based system in the prediction of submucosal invasion in endoscopic images of Barrett’s cancer. AI scored equally to international experts in the field, but more work is necessary to improve the system and apply it to video sequences and real-life settings. Nevertheless, the correct prediction of submucosal invasion in Barrett’s cancer remains challenging for both experts and AI.